1993
DOI: 10.1161/01.cir.87.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking is a major risk factor for coronary spasm.

Abstract: Background. Although there have been many studies on the risk factors for coronary artery disease, the etiology of coronary artery spasm has not yet been determined.Methods and Results. After diagnosis by coronary arteriography, various risk factors were compared between two groups of subjects using logistic regression analysis. The vasospasm group included 175

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
174
4
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(200 citation statements)
references
References 12 publications
16
174
4
6
Order By: Relevance
“…15 Smoking also enhances platelet aggregability, promotes endothelial dysfunction, and causes coronary artery vasospasm. 16 The studies of Pais et al 17 conducted in India have shown very high percentage(55%) of patients to be smokers. Hypertension is firmly established as a risk factor for IHD.…”
Section: Discussion:-mentioning
confidence: 98%
“…15 Smoking also enhances platelet aggregability, promotes endothelial dysfunction, and causes coronary artery vasospasm. 16 The studies of Pais et al 17 conducted in India have shown very high percentage(55%) of patients to be smokers. Hypertension is firmly established as a risk factor for IHD.…”
Section: Discussion:-mentioning
confidence: 98%
“…Smoking is already an established and predominant risk factor for ACS. [16][17][18] Due to poverty and lack awareness, most of these patients were irregular to take medication or unable to purchase medication to control their risk factors particularly hypertension and diabetes. Both uncontrolled hypertension and diabetes have strong influence on ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Spasms may produce endothelial damage and generate a local thrombotic process that may or may not undergo spontaneous lysis. In addition, smoking is known to be closely related to vascular spasm 21 . II) Coronary embolisms -Clinical and echocardiographic evidence gathered in this case do not support mitral valve prolapse, myxoma, or endocarditis as causes of disease in our patient.…”
Section: Discussionmentioning
confidence: 99%